PELATIHAN PEMANFAATAN MEDIA SOSIAL SEBAGAI PELUANG USAHA PADA UKM DI PULAU HARAPAN, KEP. SERIBU, JAKARTA - Purwaningsih, Nining; Lena Erdawati; Dede Sunaryo; Metha Dwi Apriyanti; Andi Kusuma Negara (JURNAL ABDIMAS PLJ, 2024)
Social media is now widely used in almost all companies, the reason is to reach consumers more quickly, easily and widely. Social media (Instagram, Whatsapp, Facebook, etc.) is part of digital marketing, namely product marketing efforts using digital media and internet networks. The change in marketing behavior from conventional to digital is not balanced by the existence of SMEs that use digital marketing, even though SMEs are believed to be able to stimulate the Indonesian economy. The methods used in this community service activity are training, lectures and questions and answers, and discussions. The result of this activity is to provide several solutions to be able to look for new business opportunities to maintain business continuity, namely utilizing social media. Apart from that, increasing digital marketing knowledge and increasing knowledge regarding the use of WhatsApp business social media as a sales promotion media. The conclusion of this activity is very useful for SMEs in providing suggestions, especially regarding digital marketing strategies.